Corrosion Resistance and Temperature Rise Tribological Properties of EP Coating Filled with Ti3AlC2 and B4C - XIAO Jialin, CHEN Yunfeng, LI Hao, SUO Xinkun, CAO Jun (Cailiao Baohu)
In order to enhance the tribological and anti-corrosion performance of copper alloy bearing bushes in methanol fuel leakage environments， an epoxy resin (EP) coating filled with Ti3AlC2 and B4C was designed and prepared on the surface of CuPb24Sn by liquid spraying method.The corrosion resistance of the composite coating was characterized by electrochemical impedance spectroscopy in a formic acid and methanol mixed solution with a volume ratio of 1:9， while its temperature rise tribological performance and wear mechanisms under complex working conditions (formic acid ＋methanol ＋lubricating oil) were investigated through high-frequency reciprocating friction-wear tests.Results showed that the Ti3AlC2- and B4C-filled EP coating exhibited excellent corrosion resistance.Under the formic acid ＋methanol ＋lubricating oil condition， the coating’s friction coefficient decreased with rising temperature， whereas its wear rate increased.At 75 ℃， the wear scar became wider than at 25 ℃， with evident ploughing effects observed on the worn surface.Materials Studio software was used for simulation calculation， and it was found that the decrease in shear strength of epoxy resin with increasing temperature was the main reason for the change in wear rate of coating.